Dealing with a Florida Winter Weather Event - Randall Cantrell; Judy Corbus; Michael Spranger (EDIS)
People in Florida might not consider planning and preparing for winter weather events because of its normally mild temperatures. However, some northern Florida regions experience temperatures below freezing and occasional snow and ice storms during the winter months. These storm events can be dangerous and even deadly. These simple safety reminders can help you and your family be better prepared for Florida’s winter weather events. This 3-page fact sheet was written by Randall Cantrell, Judy Corbus, and Michael Spranger, and published by the UF Department of Family, Youth and Community Sciences, April 2014.